Assessment of Co-heating Test - A Practical Method to Evaluate the In-situ Heat Transfer Coefficient in Dwellings - Brycke, Emma; Nilssen, Jannicke (My University, 2015)
According to the National Board of Housing, Building and Planning in Sweden, a finished constructed building should be verified to ensure that the built performance fulfil the requirements set by BBR. For the transmission losses, only theoretical calculations are used as verification, as there are no standard methods used for practical measurements. This means that in reality when the building has been executed the theoretical value might not correspond with the actual in-situ performance, meaning that there is a gap between the theoretical value and the actual built performance. However, some few methods for measuring the built thermal performance exist but they have never been established since the research has not made sufficient progress. One of the methods that exist is the Co-heating test. Recently renewed interest regarding characterization of the energy performance of buildings has led to further research and development of the test methods, and it is also the driving force behind this study. The purpose of this study was to assess the Co-heating method and examine the possibilities of measuring the built thermal performance of a building envelope by using the original Co-heating method as basis. The average heat transfer coefficient of a building was obtained and compared with a theoretical calculated value. The usability, the reliability and the future outlook of the method are the three different aspects that were focused on in this study. Practical measurements were performed on two test object as a part of the study. In addition to the Co-heating test, it was necessary to perform airtightness tests and thermographic tests on the objects in order to interpret and analyse the data. The measurements and analyses conducted in this study showed that there is a promising potential for the test to be used in the future. However, the current status requires more research to eliminate some of the uncertainties associated with the test method, and also to be able to truly evaluate the potential in this test and the use of the test as a standard method.
Keywords: Building Futures; Husbyggnad; Building Futures; Building Technologies